DETERMINING SPECULAR REFLECTION INFORMATION - PALERO, JONATHAN ALAMBRA; DAMODARAN, MATHIVANAN; VARGHESE, BABU (2025)
A computer-implemented method (100) is described. The method comprises receiving (102) first and second imaging data obtained by an imaging system (204) of a subject (202) illuminated by first illumination (206a) in a first spectral band and second illumination (206b) in a second spectral band comprising different spectral content to the first spectral band. The second illumination incident on the subject is polarized. The received first imaging data is obtained within the first spectral band. The received second imaging data is obtained within the second spectral band. The first and second illumination are admitted, via an imaging system polarizer (310) of the imaging system, into the imaging system depending on a polarization state of reflected first and second illumination received by the imaging system after reflection from a surface of the subject. Information regarding specular reflection from the surface of the subject is determined by comparing the first and second imaging data.